The Use of Clozapine In An Asian Child With Schizophrenia - Amer Siddiq, A.N.; Pillai, S.K.; Hashim, A.H. (2008)
Introduction: This is a report of an Asian child with schizophrenia on clozapine. Clozapine is often used as the last line treatment for patients with schizophrenia. Its use in children has been strictly “off label”. In our Psychiatry Adolescent and Child Unit (PAC) in University Malaya Medical Center (UMMC), we have only two children on this treatment of which one will be highlighted in this report. Objective: To report a unique experience on the use of clozapine in an Asian child. Method: A case report study.